2001
DOI: 10.1044/1092-4388(2001/030)
|View full text |Cite
|
Sign up to set email alerts
|

The Young Child's Awareness of Stuttering-Like Disfluency

Abstract: The emergence of awareness of stuttering has been an important factor in theoretical and clinical considerations for early childhood stuttering. The present research program is aimed at studying the development of awareness of stuttering-like disfluency in normally fluent preschool and first-grade children using responses to video speech samples. A total of 79 children in five different age groups were asked to discriminate between the speech (fluent and disfluent) of two puppets, identify with the one who spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
74
3
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(87 citation statements)
references
References 32 publications
6
74
3
4
Order By: Relevance
“…Similar to the findings of Culatta and Sloan (1977), Ezrati-Vinacour et al (2001) found that few of the 6-and 7-year-old children could label disfluent speech as stuttering. However, children as young as 3 years of age were able to identify and discriminate between the fluent and stuttered speech.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to the findings of Culatta and Sloan (1977), Ezrati-Vinacour et al (2001) found that few of the 6-and 7-year-old children could label disfluent speech as stuttering. However, children as young as 3 years of age were able to identify and discriminate between the fluent and stuttered speech.…”
Section: Introductionsupporting
confidence: 84%
“…The researchers found the children perceived the puppet with moderate stuttering more negatively than the puppet with fluent speech. In contrast to findings of Ezrati-Vinacour et al (2001), the children did not show a preference toward the puppet they would choose as a friend. In addition, the authors found the personality traits of the puppet with moderate stuttering were not perceived any more negatively than the fluent puppet.…”
Section: Introductioncontrasting
confidence: 84%
See 1 more Smart Citation
“…This hypothesis is tenable because awareness of stuttering develops in children from two years of age (Ambrose & Yairi, 1994;Boey et al, 2009;Yairi, 1983) and negative evaluation of stuttering is exhibited by four year old children (Ezrati-Vinacour, Platzky, & Yairi, 2001). Further, some stuttering preschool children experience negative peer responses and social interactions with peers as a consequence of their stuttering (Bernstein Ratner, 1997;Langevin, Packman, & Onslow, 2009Onslow, Attanasio, & Harrison, 2003;Yairi, 1983).…”
Section: Early Stuttering Temperament and Anxiety: Two Hypothesesmentioning
confidence: 94%
“…A statistically significant difference in the scores on the Communication Attitude Test (CAT) between the six-year-old children who stutter (CWS) and those whose speech is fluent (CWNS), led the researchers to hypothesize that the presence of a difference in communication attitude before the age of six was very likely [4]. The fact that children as young as age three years perceive the difference between fluent and non-fluent speech [10,11], and indicate a preference of a fluent communication partner over a dysfluent one, already pointed to the presence of awareness of stuttering at this young age. These data, together with the fact that a negative belief surrounding communication among CWS is already present at the age of six and becomes increasingly more negative with age [4] highlight the impact that negative communication attitude can have on CWS.…”
Section: Introductionmentioning
confidence: 99%